Size Effect upon Solidification of Small Bismuth Particles - Gladkikh, N.T.; Dukarov, S.V.; Kryshal, A.P.; Larin, V.I. (My University, 1998)
Electron microscopy was used to study the dependence of the crystallization temperature on the particle size upon solidification of small bismuth particles produced by vapor deposition on substrates of amorphous carbon. The crystallization temperature for particles 2–100 nm in diameter was found to decrease with decreasing diameter of the particles; and for particles 2–3 nm in diameter, supercooling was equal to zero. The results were analyzed within the classic theory of solidification; it was shown that, for the smallest particles, a size effect consisting in the change of the character of the liquid-crystal phase transition is observed.
Keywords: Thin films; Supercooling; size effect